Effect of SiC nanoparticles on the wear and corrosion resistance of Ag-Si composite coatings prepared by electrodeposition technique - F. Bakhtiarifard; N. Nayebpashaee (Applied Surface Science Advances)
This study aims to improve the corrosion and wear resistance of Ag-Si-SiC composite coatings by pulse-reverse electrodeposition and the addition of SiC nanoparticles. The effects of important parameters such as SiC nanoparticles, direct current, and pulse reverse electrodeposition on the microstructure, wear, and corrosion resistance of Ag-Si-SiC coatings were investigated. The coatings were evaluated using different characterization techniques such as SEM, EDS, XRD, XRF, LSV and electrochemical analysis. In addition, the pin-on-disk method and Vickers microhardness were developed to investigate the wear behavior. The coating process resulted in coatings with a target thickness of 30–40 µm, which were accompanied by a significant improvement in surface quality. This improvement was reflected in the roughness reduction from 251.4 µm to 107.8 µm. The results of the analyses showed that coatings with a Si content of 0.3 % exhibited a reduction in grain size from 20 µm to 1.2 µm and a subsequent reduction in corrosion current strength from 478×10−8 A.cm−2 to 7.31×10−10 A.cm−2 in the artificial human sweat electrolyte. The addition of 4 g/L SiC nanoparticles resulted in increased wear resistance, as indicated by a decrease in the friction coefficient from 0.5 ± 0.05 to 0.4 ± 0.03 while maintaining the same corrosion resistance. The remarkable performance of the coatings was observed under exposure to corrosive ammonium sulfide electrolytes and artificial human sweat, illustrating the effectiveness of pulsed reverse electrodeposition in producing dense, fine-grained structures of Ag-Si-SiC composite coatings, resulting in increased mechanical and corrosion resistance.